EFEKTIVITAS Spodoptera Litura Multiple Nukleopolyhedrosis Virus) YANG DIPAPARI DENGAN SINAR ULTRAVIOLET-C DAN SINAR MATAHARI TERHADAP KEMATIAN Spodoptera litura Fabr. - Mahanani Tri Asri, ; Sri Kentjananingsih, ; Yuni Kristiningsih, (Matematika dan Sains, 2009)
The propose of research was to compare the effectivity of UV-exposed and sunray-exposed SpLtMNPVs against the mortility of S. litura larvae. This experiment is designated in laboratory with completely randomized design for differentiating the effectivity of SpLtMNPV which have been 12, 16, 24 hours sunray exposed and 8 hours UV-C lamp to the mortality of S. litura F. larvae. There were 6 repetition for each group with the SpLtMNPV concentration as much as 107 PIBs/ml, so there are 24 experiment units. Each treatment includes 10 3rd instar of S. litura F. larvae. The results of research showed that sunray exposure has decreased the effectivity of SpLtMNPV viruses faster than UV-C exposure. This was showed through the fewer S. litura larvae has been killed by sunray exposed viruses than by the U.V. exposed viruses. On the 8th day application, there was only 52 - 55% larvae killed by sunray exposed viruses compared to 78% larvae killed by UV exposed viruses.rd instar of S. litura F. larvae. The results of research showed that sunray exposure has decreased the effectivity of SpLtMNPV viruses faster than UV-C exposure. This was showed through the fewer S. litura larvae has been killed by sunray exposed viruses than by the U.V. exposed viruses. On the 8th day application, there was only 52 - 55% larvae killed by sunray exposed viruses compared to 78% larvae killed by UV exposed viruses.